2005
DOI: 10.1080/13504620500081129
|View full text |Cite
|
Sign up to set email alerts
|

Free‐choice environmental learning: framing the discussion

Abstract: Education is a lifelong endeavor; the public learns in many places and contexts, for a diversity of reasons, throughout their lives. During the past couple of decades, there has been a growing awareness that free-choice learning experiences -learning experiences where the learner exercises a large degree of choice and control over the what, when and why of learning -play a major role in lifelong learning. Worldwide, most environmental learning is not acquired in school, but outside of school through free-choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(187 citation statements)
references
References 26 publications
(22 reference statements)
3
161
0
9
Order By: Relevance
“…Professional development activities outside of the school, such as museum visits or field trips, can provide teachers with authentic experiences (Falk 2005;Neathery 1998) that could enhance their practice. While these contexts are not readily considered as a means of teacher PD, research has indicated that field trips for science teachers can contribute to the enrichment of science learning environments for their students (Nugent et al 2012;Tal 2001).…”
Section: Professional Developmentmentioning
confidence: 99%
“…Professional development activities outside of the school, such as museum visits or field trips, can provide teachers with authentic experiences (Falk 2005;Neathery 1998) that could enhance their practice. While these contexts are not readily considered as a means of teacher PD, research has indicated that field trips for science teachers can contribute to the enrichment of science learning environments for their students (Nugent et al 2012;Tal 2001).…”
Section: Professional Developmentmentioning
confidence: 99%
“…It has also been suggested that the potential for learning in zoos is heightened if animals are housed and fed in as natural/realistic a manner as possible (Ballantyne, et al 2007;Smith and Broad 2008;Fernandez, et al 2009). The key to the success of the transfer of conservation messages rests with the informal learning environment of the zoo that enables individuals to freely choose what and how to learn in a process that has been called "free-choice learning" (Falk 2005).…”
mentioning
confidence: 99%
“…The learning then may be governed by individuals' or groups' needs and motivations (Brookfield, 1986;Falk & Dierking, 2002). These settings provide important experiential learning opportunities; for example, in promoting eco-literacy (knowledge, attitudes and behaviours) that can supplement learning within formal contexts (Falk, 2005). Therefore free-choice educational contexts, such as nature-based visitor centres, can offer the opportunity to complement and reinforce indoor and outdoor experiences, and bring about positive and lasting outcomes that can potentially be life-changing, by promoting reflection and meaningmaking processes around socio-ecological issues (Ballantyne & Packer, 2005.…”
Section: Free-choice Educational Settingsmentioning
confidence: 99%